MARKETING STRATEGY FOR INDONESIAN PALM OIL PRODUCTS IN ISLAMIC ECONOMIC PERSPECTIVE IN PPKS MARIHAT - Riski Ardila; Imsar Imsar (Jurnal Manajemen, 2023)
This research aims to determine the sales strategy for palm oil products from an Islamic Economics perspective. The integration of conventional marketing into sharia principles refers to efforts to combine conventional marketing strategies with Islamic economic perspectives. In collecting data, this type of research uses qualitative research with subjective strategies using library or literature study methods, especially information gathering methods by understanding and focusing on speculation from various related articles as well as interviews and observations. The results of this research show that by implementing a sales strategy that adheres to the principles of Islamic economics, a business will be able to build a strong image and gain consumer trust and not harm consumers and become a sin for producers.